Interactive whiteboards in andean communities: A training model - Zúñiga Torres, Juan Carlos (2021)
Interactive whiteboards are an educational tool widely adopted as part of the integration of Information and Communication Technologies (ICT) and cost reduction. This technology becomes more effective when teachers know and apply interactive teaching methods that can improve the results of the teaching-learning process. This research presents a training model for primary and high school teachers in Yanaquihua, Condesuyos, Arequipa. The proposed training model generated good results: teachers improved their interactive content-making skills by 29 percent. Also, 50 percent of the interactive content created by teachers is considered satisfactory quality. Only 11 percent of teachers needed to dedicate more effort to achieve the objectives. This document reports the importance, the limitations, and the results of applying the proposed training model to improve the performance and effectiveness of technologies in the classroom. Keywords-- Interactive whiteboard; training model; Andean communities; teachers’ training; interactive content.